Gold atom-decorated CoSe2 nanobelts with engineered active sites for enhanced oxygen evolution. Issue 38 (15th September 2017) - Zhao, Xu; Gao, Pengfei; Yan, Yu; Li, Xingqi; Xing, Yulin; Li, Hongliang; Peng, Zhenmeng; Yang, Jinlong; Zeng, Jie
Abstract : Isolated Au atom-decorated CoSe2 nanobelts with strengthened H2 O adsorption and sufficient exposure of active sites for enhanced oxygen evolution. Abstract : Electrochemical water splitting is greatly hindered by the kinetically sluggish oxygen evolution reaction (OER). The development of economical and efficient catalysts with precisely modulated active sites is crucial for exploring the reaction mechanism and promoting the water oxidation process. Herein, we present isolated Au atom-decorated CoSe2 (Au1 –CoSe2 ) nanobelts with precisely engineered active sites for an enhanced OER. Theoretical investigations showed that the decoration of isolated Au atoms could shift up the d-band center and thus lower the H2 O adsorption energy of Co active sites. Moreover, the trace amount of Au atoms (0.1 wt%) also ensures the effective exposure of Co active sites and minimizes the use of Au. Both the intrinsically enhanced H2 O adsorption and the sufficient exposure of active sites contributed to the remarkable electrocatalytic performance of the Au1 –CoSe2 nanobelts. The as-prepared Au1 –CoSe2 nanobelts exhibited a 21.1-fold, 5.7-fold, and 1.9-fold higher OER activity relative to pure CoSe2 nanobelts, Au nanoparticle-deposited CoSe2 (AuN –CoSe2 ) nanobelts, and commercial Ir/C, respectively. This study demonstrates the validity of atomic-scale control of active sites in Co-based catalysts, which could also be extended to the design of highly efficient catalysts for other energy-related processes.